Multiparty Conversations With People With Congenital Deafblindness: Operationalization, Significance, and Requirements - Worm, Mijkje; Damen, Saskia; Minnaert, Alexander; Janssen, Marleen J. (Frontiers in Education, 2020)
Typically developing children are exposed to multiparty communication on a daily basis from birth. This facilitates both group belonging and observational learning. However, involvement in multiparty conversations is not self-evident for people with congenital deafblindness due to their dual sensory impairment. This study explored the added value of multiparty conversations for people with congenital deafblindness by analyzing communication partners’ narrations of their experiences. Three focus group sessions were conducted with professionals and relatives (n=24) of people with congenital deafblindness. These sessions were audiotaped, transcribed, and coded using thematic analysis. Participants described the following defining characteristics of multiparty conversations in relation to congenital deafblindness: a minimum of three people involved, with at least one who has congenital deafblindness; awareness of the presence of the other communication partners; attention for the communicative setting; and the use of communication means that are familiar to all communication partners. In their experience, multiparty conversations supported social, emotional, and communication development. Furthermore, focus group participants indicated that spontaneous multiparty conversations with people with congenital deafblindness were scarce and, therefore, needed to be encouraged by communication partners. The participants considered positive beliefs, preparation of the multiparty conversation, repetitions, and a low communication speed as important partner competencies to support the involvement of individuals with congenital deafblindness in multiparty conversations. Accordingly, we recommend the development of an intervention protocol for communication partners to initiate and foster multiparty conversations with people with congenital deafblindness. Another recommendation is to test the effects of MPC on the observational learning of people with congenital deafblindness.